Active lower limb prosthetics: a systematic review of design issues and solutions. Issue 3 (December 2016) - Windrich, Michael; Grimmer, Martin; Christ, Oliver; Rinderknecht, Stephan; Beckerle, Philipp
Abstract This paper presents a review on design issues and solutions found in active lower limb prostheses. This review is based on a systematic literature search with a methodical search strategy. The search was carried out across four major technical databases and the retrieved records were screened for their relevance. A total of 21 different active prostheses, including 8 above-knee, 9 below-knee and 4 combined knee-ankle prostheses were identified. While an active prosthesis may help to restore the functional performance of an amputee, the requirements regarding the actuation unit as well as for the control system are high and the development becomes a challenging task. Regarding mechanical design and the actuation unit high force/torque delivery, high efficiency, low size and low weight are conflicting goals. The actuation principle and variable impedance actuators are discussed. The control system is paramount for a "natural functioning" of the prosthesis. The control system has to enable locomotion and should react to the amputee's intent. For this, multi-level control approaches are reviewed.